PEMAHAMAN ANAK TAMAN KANAK-KANAK TK INTEGRAL YAA BUNAYYA TENTANG KEBIASAAN MENCUCI TANGAN DALAM KEHIDUPAN SEHARI-HARI - Kiki Rizki Aulia; Sri Rahmawati; Mariati; Muhd Firmansyah (Akademi Kebidanan Harapan Bunda Bima, 2026)
This study aims to explore kindergarten children's understanding of handwashing habits in their daily lives. Cultivating handwashing habits is a form of clean and healthy living behavior that is crucial to instill from an early age to prevent various diseases. This study employed a qualitative method with a phenomenological approach. The research subjects consisted of 10 children aged 5–6 years at KB TK Integral Yaa Bunayya, 2 classroom teachers, and 3 parents as supporting informants. Data were collected through observation and semi-structured interviews. Data analysis followed the Miles and Huberman model, which includes data reduction, data display, and drawing conclusions.The results indicate that most children understand that handwashing aims to maintain cleanliness and prevent illness. The children are aware of critical times to wash their hands, such as before eating, after playing, and after using the toilet. However, their understanding remains simple and concrete, aligned with early childhood developmental stages. This study also found that habituation, direct modeling, and the roles of teachers and parents significantly influence children's handwashing behavior. Therefore, consistent and engaging health education is vital in shaping clean and healthy living habits in early childhood. .